Microstructures of Early Cretaceous belemnite rostra and their diagenesis. (September 2022) - Stevens, Kevin; Mutterlose, Jörg; Ohnemus, Bernhard; Idakieva, Vyara; Ivanov, Marin
Abstract: Microstructures of belemnites are still poorly understood for many species, which may have wide-ranging implications for their palaeobiology and geochemical application. We acquired microscopical and geochemical data of taxonomically distinct co-occurring belemnites from the lower Aptian of Bulgaria and Germany. The rostra display consistent macroscopical, microscopical, and geochemical differences. Belemnopseid specimens ( Mesohibolites sp., Neohibolites ewaldi ) are well-preserved, apart from an originally porous, primarily organic-rich, and fine-grained section in the anterior part of the rostra, which was recrystallized and cemented during diagenesis. The results of the Aptian taxa are compared to the Hauterivian belemnopseid Hibolithes jaculoides . Dissolution/erosion of the anterior sections of these rostra is known to form a pseudoalveolus. In contrast to the belemnopseids, major parts of Duvalia grasiana specimens are recrystallized due to an originally high content of organic matrix. Such diverse belemnite microstructures must be considered in geochemical studies. Their palaeobiological background is discussed in terms of the modification of hydrostatic stability. Originally porous, primarily organic-rich anterior rostra might represent a synapomorphy of a group of belemnites containing at least some species of the Belemnopseidae as well as potentially further derived belemnite taxa.